Transformational Leadership for Department Heads at the University of Mohamed Seddik Ben Yahia, Algeria - Kaouache, Raouf; Yaiche, Ousila; kaouache, Jamal Aldin (Al-Adab Journal, 2020)
This research examines the extent to which transformational leadership degree is existed in Algerian universities with a special focus on the head of departments at University of Mohammed Seddiq Ben Yahia, Algeria. In addition, it aims to identify the differences according to their personal and professional characteristics. Data were collected from 144 faculty members via a questionnaire form. SPSS software program is employed for data analysis purposes. Findings revealed a moderate degree of transformational leadership existence among head of departments. Furthermore, Faculty members decreasingly ranked transformational leadership dimensions as inspirational motivation, idealized influence, intellectual stimulation and individualized stimulation. Moreover, the study found insignificant differences in transformational leadership degree due respondents’ demographics. Meanwhile, significant differences associated with seniority were revealed. Implications for Algerian universities are also discussed.